The Foundation of the Kalmyk Cavalry Corps - Ryszard Sodel (Review (Institute of National Remembrance), 2023)
The aim of this article is to present the history of the foundation of the Kalmyk Cavalry Corps and its combat activities from August 1942 to May 1945. The author will first present the history of the Kalmyk nation and their relations with the tsarist state from the 17th to the 20th century, followed by their social, political and economic situation within the USSR. The next part examines the activities of the Soviet authorities in the period from June 1941 to July 1942, when the Kalmyk Autonomous Soviet Socialist Republic was incorporated into the Soviet Union’s war economy. The author then explores the reasons behind the formation of this collaborative unit composed of Soviet citizens, as well as the founder of the Corps and its first commander, Otto Vierba, alias Dr. Doll, a mysterious personality. The article outlines his combat journey in the years 1942–1944, leading through the steppes to the Volga region and Ukraine. The last part of the article presents the activities of the Kalmyk Cavalry Corps in the years 1944–1945, including its participation in anti-partisan operations in the Podkarpacie and Lublin regions as part of the Grosseinsatz Maigewitter, Sturmwind I, Sturmwind II and Wirbelsturm operations. The article then describes the organisational changes and political activities of the Kalmyk National Committee, which led to its accession to the Committee for the Liberation of the Nations of Russia (Комитет освобождения народов России, Komitet osvobozhdeniya narodov Rossii, KONR). It also presents the group’s combat actions in the Kielce region of the German-occupied Poland from the end of the summer of 1944 to January 1945, during which it faced heavy struggles as it was retreating before the advancing Soviet troops. The group ended its combat trail in Austria in May 1945, subordinated to the 15th SS Cossack Cavalry Corps.